Status of address spoofing attack prevention techniques in software-defined networking (SDN). (17th November 2021) - Meena, Ramesh Chand; Meena, Keshav; Kumar, Ankit; Gupta, Mukesh; Kumar, Santosh
Abstract: The numerous benefits of software-defined networking technology are enticing businesses to use it. Simple forwarding devices that support the OpenFlow protocol send data packets across the network data plane and control plane. The flight control plane is managed using SDN control. A forwarding device sends a data packet from the source host to the destination, using the address information from the packet in process. Before sending any data, the device will first check to see if the originating host address is valid. The SDN controller monitors data packet flows and makes the necessary entries in the device's flow route. Hosts are unable to send data packets because there is no first flow entry. The forwarding device sends this data packet to the controller. As a result of this analysis, the controller creates the relevant flow entry in the device's flow table. If this is the case, fake source address attacks could be used to wreak havoc on the network. This article investigates the current state of SDN attack avoidance solutions for SDN configuration and provides a review of such tactics.